Vrouwen van Nederland - Komrij, Gerrit (Amsterdam : Uitgeverij Voetnoot, 2001)
Dukkers, Hans ; Blazer, Carel ; Besnyö, Eva ; Huf, Paul ; Presser, Sem ; van Zachten, Eli ; Romein, Annelies ; Jonker, Henk ; Gerritsen, Frits ; Suister, Ed ; Austria, Maria ; Windig, Ad; ed al.
Schenking Eric de Kuyper
boek